2013
DOI: 10.1097/pep.0b013e3182a74398
|View full text |Cite
|
Sign up to set email alerts
|

Low-Cost Virtual Reality Intervention Program for Children With Developmental Coordination Disorder

Abstract: Purpose:To explore the feasibility of using a low-cost, off-the-shelf virtual reality (VR) game to treat young children with developmental coordination disorder (DCD) and to determine the effect of this intervention on motor function. Methods: Nine children, aged 4 to 6 years, referred to physical therapy because of suspected DCD participated in 10 game-based intervention sessions. Outcome Measures: Outcome measures included Movement Assessment Battery for Children-2 (M-ABC-2), the DCD Questionnaire (DCD-Q), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
63
0
6

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(69 citation statements)
references
References 40 publications
0
63
0
6
Order By: Relevance
“…Various studies have already demonstrated the efficacy of intervention programs based on virtual reality for these children [19,20,35,36,[21][22][23][24][31][32][33][34], but the absence of further protocol systematization has been an important hindrance for professionals and researchers in this field to clearly understand the impact of such interventions on children's activity performance. [19,[22][23][24] are scarce, and their results tend to demonstrate that despite the benefits of virtual reality, conventional interventions seem to be more effective in the improvement of motor performance of children with DCD [19,[22][23][24]. Due to limitations and differences between the protocols adopted, though, these results must be interpreted carefully.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have already demonstrated the efficacy of intervention programs based on virtual reality for these children [19,20,35,36,[21][22][23][24][31][32][33][34], but the absence of further protocol systematization has been an important hindrance for professionals and researchers in this field to clearly understand the impact of such interventions on children's activity performance. [19,[22][23][24] are scarce, and their results tend to demonstrate that despite the benefits of virtual reality, conventional interventions seem to be more effective in the improvement of motor performance of children with DCD [19,[22][23][24]. Due to limitations and differences between the protocols adopted, though, these results must be interpreted carefully.…”
Section: Discussionmentioning
confidence: 99%
“…The handful of existing studies that compare interventions with and without virtual reality for children with DCD still show limitations about evidence created by the virtual reality intervention [19,[21][22][23][24].…”
mentioning
confidence: 99%
“…The protocol is based on the domains of the MABC-2 domains. Various studies have already demonstrated the efficacy of intervention programs based on VR for these children [19][20][21][22][23][24][31][32][33][34][35][36], but the absence of further protocol systematization has been an important hindrance for professionals and researchers in this field to clearly understand the impact of such interventions on children's activity performance.…”
Section: Discussionmentioning
confidence: 99%
“…The handful of existing studies that compare interventions with and without VR for children with DCD still show limitations about evidence created by the VR intervention [19,[21][22][23][24]. Moreover, it is not clear whether one type of intervention offers greater gains than the other due to the shortcomings from the scarce previous studies already published.…”
Section: Introductionmentioning
confidence: 99%
“…41 Children showed significant post-intervention improvements on balance and motor outcomes on the Movement Assessment Battery for Children (2 nd Edition). Results demonstrated the feasibility of balance training using components similar to our STABEL system.…”
Section: Introductionmentioning
confidence: 97%